Christian perspectives on human development - Aden, Leroy; Benner, David G.; Ellens, J. Harold, 1932- (Grand Rapids, MI Baker, 1992)
Includes bibliographical refrences and indexes.
Keywords: Christianity -- psychology; Developmental psychology -- religious aspects -- Christianity; Maturation (psychology) -- religious aspects -- Christianity; Belief and doubt